Strategi Perancangan Brand Campaign untuk Penguatan Brand Awareness melalui Iklan Digital Platform Vidio.Com - Rifalsyah, Fahriza; Saleh, Amiruddin (Asosiasi Ide Bahasa Kepri, 2025)
The shift in media consumption toward digital platforms has created new opportunities for Brands to strengthen awareness through over the top (OTT) services. Vidio.com, as a leading local OTT platform, provides a strategic medium for delivering effective digital advertising. This study aimed to (1) analyze the implementation of brand campaign strategies to enhance brand awareness on Vidio.com, (2) examine the application of campaign design elements, including audience identification, media objectives, media selection, budget allocation, scheduling, and evaluation, and (3) explore challenges faced by the Campaign Management division and the solutions applied. The study employed Belch and Belch’s (2001) media planning theory and used a qualitative descriptive approach through observation, interviews, active participation, and literature review. Findings revealed that integrated campaigns combining multiple ad formats and collaborations with original content effectively enhanced brand awareness. Strategic audience segmentation, media planning, budget allocation, scheduling, and evaluation ensured campaign success. Challenges such as limited inventory, time constraints, client brief changes, and cross team coordination were addressed through flexible strategies, dedicated persons in charge, and efficient communication. Based on these findings, the study recommends strengthening internal workflow through clear PIC assignments for each campaign, enhancing collaborative work systems, and maintaining fast and flexible communication practices to support smoother execution and optimize the effectiveness of future campaigns on digital OTT platforms.